ANALISIS MODAL KERJA DALAM MENINGKATKAN PERTUMBUHAN LABA BERSIH PT. PERKEBUNAN NUSANTARA IV MEDAN - Ihsan Rambe (Institut Agama Islam Negeri Padangsidimpuan, 2017)
Working capital is the main factor driving the company’s operations. The purpose of the study was to ascertain the management of working capital in the company, PT. Perkebunan Nusantara IV, was able to increase the net profit growth. The method used descriptive research with quantitative approach.The results of the analysis in 2011-2015 showed that the working capital in 2013 and 2015 decreased. Net profit growth in 2012,2013 and 2015 showed decreased too.